2018
DOI: 10.1590/1980-57642018dn12-020015
|View full text |Cite
|
Sign up to set email alerts
|

High levels of alexithymia in patients with multiple sclerosis

Abstract: Alexithymia is a personality trait characterized by difficulties identifying and describing feelings. Some researchers describe high levels of alexithymia among patients with multiple sclerosis (MS) but literature data on this subject are scarce.Objective:The objective of the present study was to characterize findings of alexithymia in patients with MS.Methods:This cross-sectional case-control study included 180 patients with MS and a matched control group. Data for patients with MS included disease duration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 13 publications
5
16
0
1
Order By: Relevance
“…First, alexithymia was associated with lower education, a finding that is consistent with some [25], but not all MS studies (for reviews see [1]). Individuals with higher education might have better language skills to verbalize their feelings, rendering them less alexithymic than those with lower education.…”
Section: Sociodemographic Clinical and Neuropsychological Datasupporting
confidence: 68%
“…First, alexithymia was associated with lower education, a finding that is consistent with some [25], but not all MS studies (for reviews see [1]). Individuals with higher education might have better language skills to verbalize their feelings, rendering them less alexithymic than those with lower education.…”
Section: Sociodemographic Clinical and Neuropsychological Datasupporting
confidence: 68%
“…Alexithymia scores were higher in women in the MS group and men in the control group. Eboni et al [16] (2018) found higher alexithymia scores in MS women patients while Levant et al [21] (2009) found higher alexithymia scores in healthy men. Unlike our study Kuloğlu et al (2013) found no significant difference between alexithymia scores considering gender differences.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Hyunyoung et al [15] (2012) found similar results in their Korean study. Eboni et al [16] (2018) also studied 180 Brazilian and found that alexithymia scores were significantly higher in patients suffering from both depression and MS.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the EQ-5D is subjective and selfreported. This is important to capture the impact of a condition on a patient but relies on their ability to identify and recognize their feelings, an ability often impaired (known as alexithymia) in MS 16 , and patients' recall, which may be limited by cognitive dysfunction. Self-report may therefore be inappropriate in MS because if patients cannot recognize their own limitations they are unable to report them 17 .…”
Section: Limitations Of the Eq-5d In Evaluating Cognitive Declinementioning
confidence: 99%